HYPOGLYCAEMIC EFFECT OF THE METHANOL EXTRACT OF IRVINGIA GABONENSIS SEEDS ON STREPTOZOTOCIN DIABETIC RATS. - Ngondi, Judith Laure; Djiotsa, Emile Joachim; Fossouo, Zephyrin; Oben, Julius (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
The hypoglycaemic effect of the methanol extract of Irvingia gabonensis seeds (Irvingiaceae) was examined in streptozotocin-diabetic rats. A single oral administration of the methanol extract at doses of 150 and 250mg/kg significantly (P < 0.001) lowered the plasma glucose levels in diabetic rats two hours after treatment.